« Bois ! ». La rencontre fatale entre Salammbô et Mâtho dans les transpositions iconiques du roman - Bruna Donatelli (Flaubert: Revue Critique et Génétique)
The encounter between Salammbô and Mâtho, the two main characters in Flaubert’s Carthaginian novel, is marked by a daring gesture by Hamilcar Barca’s daughter which will ultimately cost both of them their lives. In the course of a licentious feast of the mercenaries who are rising up because they have not received their agreed payment, the Carthaginian princess offers the Libyan chief a goblet of wine; her purpose is unclear: fatal attraction or a ploy to soothe the rage of the mercenaries? The development of the avant-textes of the novel suggests some hesitation in this respect. Salammbô’s gesture is therefore not casual in the economy of the novel. The goblet is in fact a stylistic device of primary importance, which nourishes and gives substance to the plot, triggering desire, power, sex and death. For this scene Flaubert draws inspiration from Amédée Thierry’s Histoire des Gaulois, drawing attention to how for those ancient peoples such a gesture on the part of a woman would represent essentially a choice of groom and future husband. Salammbô’s action is referred to in the novel in the dialogues of some of the mercenaries, but remains wrapped in an aura of sacred mistery which leaves the reader intentionally at a loss. Its transposition in images is accordingly problematic. As a result, in the iconic transpositions of the novel this first and brief encounter between the two characters is often left in the background, while focusing on the scene of love and violence/rape under the tent of the mercenary. Among the numerous illustrated editions and comic strip adaptations of the novel, this paper examines the iconic tranpositions by Rochegrosse, Bussière, Blaine, Lagneau and Druillet, who all display profound literary perceptiveness and have successfully enhanced the episode in question, establishing with the text an empathic relationship and a dialogue which opens up new and original interpretations.